Computational-aided drug design strategies for drug discovery and development against oral diseases - Wu, Tong; Jiang, Wentao (Frontiers in Pharmacology, 2025)
Oral diseases, including dental caries, periodontitis, oral cancer, and mucosal infections, significantly impact overall health, underscoring the need for effective drug development. However, the discovery of novel oral drugs remains challenging due to complex disease mechanisms and limitations in traditional drug screening methods. Computer-aided drug design (CADD) has emerged as a powerful technology to accelerate drug discovery by improving efficiency and reducing costs. This review explores the application of CADD in the development of peptide-based drugs, small molecules, and plant extracts for oral diseases. It discusses CADD-associated antibacterial, anti-inflammatory, anticancer, and tissue regeneration therapies, highlighting available models, online tools, and successful case studies. Additionally, this review examines the intersection of CADD with natural product-based drug discovery, expanding therapeutic possibilities. While CADD enhances drug discovery, challenges such as mismatches in virtual screening and the need for experimental validation remain to be overcome. Despite these limitations, CADD is gaining traction in oral medicine, with the potential to revolutionize treatment strategies. This review aims to inspire further research and promote innovative therapeutic approaches to improve oral health and patient outcomes by summarizing recent advancements and emerging trends.